Traditional beliefs and practices of postpartum care in rural East Nusa Tenggara, Indonesia - Toy, Sarci Magdalena; Ndoen, Enjelita Mariance; Ndun, Helga Jilvera Nathalia (International Journal of Public Health Science (IJPHS), 2024)
Maternal mortality remains a pressing public health issue in Indonesia, particularly for mothers residing in rural regions who often forego postnatal health services due to traditional beliefs and practices. This qualitative research delved into the cultural perspectives of the local community to gain insight into the care practices of postpartum mothers in rural areas of NTT Province, Indonesia. The study involved in-depth interviews with nine participants, including four postpartum mothers, four family members, and one village midwife, with the interview data analyzed thematically. The research revealed that cultural beliefs and practices revolving around the postpartum period in NTT align with shared beliefs and traditional practices found in various Asian societies. This includes behavioral taboos and food restrictions. The study also identified two primary postpartum traditions aimed at restoring the postpartum mother's body heat and strength. All postpartum mothers adhere to traditional care practices because they believe in their benefits, pressure from family members, and fear of non-compliance consequences. However, postnatal mothers and their families have low postnatal care visits and do not receive adequate information about postpartum care. Health literacy for postpartum women and their families in rural areas needs to be improved and health workers should provide culturally sensitive maternal health services.